The deformation of the bearing surface of the bearing of the turbocharger, depending on its stiffness - Кравцов, В.І.; Кіндрачук, М.В.; Діденко, О.Л.; Бурбела, Ю.Б. (Problems of Tribology, 2016)
The methodology of research of the bearing surface elastic deformation when the forces arising in discrete steps from start to stop act simultaneously is presented by way of example of a radial sliding bearing operation in the compressor of the gas-pumping unit turbine. To this end a mathematical model describing balance and deformation of spatially curved element, as well as its external and internal geometry is used. The methodology of numerical solution of the set task is based on the general application of the continuation by a parameter method and the method of Newton-Kantorovich. The article describes the problems arising from operation of the block bearings in turbogenerator compressors and provides a literature review on this subject. It shows that the local tasks describing certain processes are used to be solved in the prob-lems of friction. Nevertheless, the process of friction is accompanied with a large number of support factors that have not yet been considered simultaneously. The methodology description provides its very essence and shows the ways to specify the possible loads that may be added or removed in the process of bearing operation. The possibility of research of support sur-face with a non-circular (oval) geometry of the axial line is shown by way of example of turbocompressor support bearing. The results of the research are presented in the charts indicating the values of some characteristics of the mode of deforma-tion of the bearing surface of the turbocompressor radial sliding bearing with specific physical and geometrical parameters in dimensionless units.